Peran Akuntansi Syariah Dalam Meningkatkan Kepercayaan Publik Melalui Nilai Keadilan Dan Kemaslahatan Lembaga Keuangan Islam - Evi Irawati Aisya. A; Putri Ameliah; Nur Aipa; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the strengthening of Islamic accounting practices in enhancing public trust through improvements in sharia compliance, governance quality, and transparency within Islamic financial institutions. Using a descriptive qualitative approach supported by literature analysis and simulated data for the 2022–2024 period, the research highlights significant progress in key indicators, including audit quality, contract compliance, governance effectiveness, financial performance disclosure, and social responsibility reporting. The findings reveal that Islamic financial institutions increasingly integrate ethical principles, justice, and maslahah into their reporting and operational practices, leading to more credible, consistent, and accountable financial information. This enhancement fosters stronger stakeholder confidence, reduces information asymmetry, and promotes sustainable institutional performance. Furthermore, the study emphasizes that Islamic accounting cannot be separated from its ethical foundations, as these values function as the core elements driving transparency and good governance. Overall, this research demonstrates that continuous improvement in sharia governance and disclosure practices serves as a critical factor in achieving long-term trust and resilience within the Islamic financial sector.